تحليل معدل التعويضات في التأمين الحكومي على المركبات في سورية - اليوسف, ندى (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يعد قطاع التأمين من أهم قطاعات الخدمات المالية في أنحاء العالم، لأنه يواكب مجمل الأنشطة الاقتصادية ويسهم في دعمها، ويحافظ على استقرارها، بالإضافة إلىالدور الاجتماعي الهام للنشاط التأميني من خلال فرص العمل التي يوفرها، أو من خلال مساهمته في الاستقرار الاجتماعي. تهدف دراستنا إلى استعراض الدور الهام للتأمين الحكومي على المركبات في سورية من خلال دراسة تحليلية لمعدل تعويضات هذا الفرع في المؤسسة العامة السورية للتأمين، لكونها المؤسسة التي تمارس التأمين الحكومي، و بيان أثر هذا التأمين في مجمل أعمالها خلال الفترة من 2007 إلى2012 . لقد تبين لنا من خلال هذه الدراسة أن قطاع التأمين الحكومي على المركبات في سورية يشكل الحصة الكبرى من حجم أعمال المؤسسة العامة السورية للتأمين وهذا ما يشير إلى ضعف في باقي فروع التأمين، بالإضافة إلى ظهور تأثير الأزمة السياسية والأمنية والاقتصادية التي تتعرض لها سورية في هذه المحفظة بانخفاض أقساطها وازدياد عدد حوادثها و بالتالي ازدياد التعويضات المدفوعة واحتياطياتها ووقوع المؤسسة في خسائر غير متوقعة . Insurance sector is considered one of the most important financial services sectors around the world, because accompanies economical activities , contributes to their support , and maintains their stability , the important social role of insurance activity is highlighted through job vacancies provided ,or through its contribution in the social stability . Our study aims to review the main important of government insurance on vehicles in Syria through analytical study the rate of compensation of such branch in Syrian Insurance Company since it is the company that practices government insurance, in addition to spot the light on insurance effect on the total business of such company from 2007 to 2012 The study can conclude that government insurance sector of vehicles in Syria constitutes the main share of business volume of Syrian Insurance Company. This indicates the weakness of other insurance branches, in addition to the emergence of the impact of political security, economic crisis experienced by Syria on such sector starting from the decrease of insurance premiums to the increase of vehicles accidents number which led to the increase of the paid compensation installments and company’s reserves which caused unforeseen losses to the company.